Physicochemical characterization and evaluation of PGA bioflocculant in coagulation-flocculation and sedimentation processes - Campos, Valquíria [UNESP]; Fernandes, Ana R.A.C. [UNESP]; Medeiros, Thales. A.M. [UNESP]; Andrade, Erik L. [UNESP] (Elsevier, 2016)
This paper analyzesanalyses the effectiveness of three commercial products: aluminum sulfate, aluminum polychloride and polyglutamic acid-based bioflocculant, in water clarification and purification. Poly-γ-glutamic acid (PGA), a naturally occurring anionic polymer, is already produced on an industrial scale. A conventional jar test apparatus was used for flocculation experiments. The tests were performed using raw water from the Salto de Pirapora Water Treatment Plant (WTP) in the state of São Paulo, Brazil. The structure and elemental composition of PGA bioflocculant, which was characterized by Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), X-ray diffraction (XRD), X-ray fluorescence spectrometry (XRF) and thermogravimetric analysis (TGA), suggests that it is basically inorganic in nature, with high contents of calcium sulfate (87%) and γ-polyglutamic acid (5%), among other chemical compounds. The performance of PGA bioflocculant was superior to that of the other coagulants. In the dry season, 80 mg L-1 of PGα21Ca removed 89.74% of apparent color, and residual turbidity was 5.78 NTU. In the rainy season, 90 mg L-1 of PGα21Ca removed 96.89% of apparent color and residual turbidity was 1.93 NTU.
Keywords: Aluminum sulfate; PGA bioflocculant; Polyaluminum chloride; Salto de pirapora WTP; São paulo